2015
DOI: 10.4187/respcare.04165
|View full text |Cite
|
Sign up to set email alerts
|

AARC Clinical Practice Guideline: Effectiveness of Pharmacologic Airway Clearance Therapies in Hospitalized Patients

Abstract: Aerosolized medications are used as airway clearance therapy to treat a variety of airway diseases. These guidelines were developed from a systematic review with the purpose of determining whether the use of these medications to promote airway clearance improves oxygenation and respiratory mechanics, reduces ventilator time and ICU stay, and/or resolves atelectasis/consolidation compared with usual care. Recombinant human dornase alfa should not be used in hospitalized adult and pediatric patients without cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
(59 reference statements)
2
25
0
4
Order By: Relevance
“…In the current trial, doses of heparin used were consistent with previous studies in burns, [1] asthma, [30] bronchiectasis [31] and cystic fibrosis. [6] The lack of effect of heparin in this study compared to previous studies may have been due to different patterns of airway inflammation seen in acutely ventilated patients or a low baseline VAP rate.…”
Section: Discussionsupporting
confidence: 69%
“…In the current trial, doses of heparin used were consistent with previous studies in burns, [1] asthma, [30] bronchiectasis [31] and cystic fibrosis. [6] The lack of effect of heparin in this study compared to previous studies may have been due to different patterns of airway inflammation seen in acutely ventilated patients or a low baseline VAP rate.…”
Section: Discussionsupporting
confidence: 69%
“…1 Lacombe et al 9 discovered, however, that mechanical insufflation-exsufflation alone may not be enough to produce adequate airway clearance. As an independent airway clearance technique, mechanical insufflation-exsufflation generates a lower cough peak flow than it does when paired with manually assisted cough and also intermittent positive-pressure breathing paired with manually assisted cough.…”
Section: Mechanical Insufflation-exsufflationmentioning
confidence: 99%
“…12 The routine use of PEP for patients with COPD is not recommended but may be an option for those patients with COPD and symptomatic secretion retention. 1 Osadnik et al 13 conducted a randomized controlled trial to study the effect of PEP added to the usual care of hospitalized subjects with COPD exacerbations. They found that adding PEP to the hospitalized pulmonary regime did not improve symptoms, quality of life, or incidence of future exacerbations.…”
Section: Pepmentioning
confidence: 99%
See 2 more Smart Citations